The Business Process Management Map – an Effective Means for Managing the Enterprise Value Chain. (2016) - Fleacă, Elena; Fleacă, Bogdan
Abstract: The paper aims to map business engineering and management with the aid of process reasoning that enables coherently integrating two essential dimensions of any industrial organization: the management, with clear responsibility for coordinating the work system and the functional areas, being in charge with executing specialized operations, according to relevant rules, regulations, and procedures. The authors proposed an effective reasoning for managing the enterprise value chain, considering a highly dynamic sector ″Cosmetic and personal care industry″ that represents a key driver for boosting the competitiveness of business market.